PENGARUH MOTIVASI BELAJAR, PERHATIAN ORANG TUA, DAN KEBUGARAN JASMANI TERHADAP HASIL BELAJAR PENDIDIKAN JASMANI OLAHRAGA DAN KESEHATAN - Dedi Aryadi (Universitas Setia Budhi Rangkasbitung, 2020)
Problems in SMPN 1 Maja students show that student learning outcomes for Sports Education and Physical Health are still below average. Student learning outcomes at SMPN 1 Maja are influenced by many factors, which are influenced by studies of parents' motivation and attention, as well as physical fitness. The purpose of this study was to determine the direct and indirect effect of variations in learning motivation, parenting, and physical fitness on learning outcomes of Physical Sports and Health Education. The research method is a quantitative approach path analysis. The population was all students at SMPN 1 Maja and all students at SMPN 3 Maja in 2020/2021, totaling 129 students. The sampling method was carried out by using Proportional Stratified Random Sampling, with a sample of 91 students. Data were collected using a questionnaire for learning motivation and parental attention, physical fitness tests for physical fitness and second semester test results for learning outcomes of Physical Sports and Health Education. The results of the data analysis showed that: (1) Motivation to learn directly affects learning outcomes of Physical Sports and Health Education by around 15%. (2) Parents' attention does not directly affect the learning outcomes of Physical Sports and Health Education. (3) Physical fitness directly affects the learning outcomes of Sports and Physical Health Education around 62.1%. (4) The study of motivation and physical fitness indirectly affects the results of physical exercise and health education around 19.2%. (5) Parents' attention and physical fitness do not indirectly affect the learning outcomes of Physical Sports and Health Education. (6) Parents' attention and learning motivation indirectly affect the learning outcomes of Sports Education and Physical Health by 16.9%. Keywords; The Role of Motivation, Exercise in improving, Physical Fitness. Abstrak Permasalahan pada siswa SMPN 1 Maja menunjukkan hasil belajar siswa terhadap Pendidikan Olahraga dan Kesehatan Jasmani masih di bawah rata-rata. Hasil belajar siswa di SMPN 1 Maja dipengaruhi oleh banyak faktor, yang dipengaruhi oleh studi motivasi dan perhatian orang tua, serta kebugaran fisik. Tujuan dari penelitian ini adalah untuk mengetahui pengaruh langsung dan tidak langsung antara variasi motivasi belajar, pengasuhan orang tua, dan kebugaran fisik terhadap hasil belajar Olahraga Fisik dan Pendidikan Kesehatan. Metode penelitian adalah analisis jalur pendekatan kuantitatif. Populasi adalah semua siswa di SMPN 1 Maja dan semua siswa di SMPN 3 Maja tahun 2020/2021 yang berjumlah 129 siswa. Metode pengambilan sampel dilakukan dengan menggunakan Proportional Stratified Random Sampling, dengan sampel 91 siswa. Data dikumpulkan dengan menggunakan kuesioner untuk motivasi belajar dan perhatian orang tua, tes kebugaran jasmani untuk kebugaran jasmani dan hasil tes semester II untuk hasil belajar Olahraga Fisik dan Pendidikan Kesehatan. Hasil analisis data menunjukkan bahwa: (1) Motivasi belajar secara langsung mempengaruhi hasil belajar Olahraga Fisik dan Pendidikan Kesehatan sekitar 15%. (2) Perhatian orang tua tidak secara langsung mempengaruhi hasil belajar Olahraga Fisik dan Pendidikan Kesehatan. (3) Kebugaran fisik secara langsung mempengaruhi hasil belajar Olahraga dan Pendidikan Kesehatan Fisik sekitar 62,1%. (4) Studi motivasi dan kebugaran fisik secara tidak langsung mempengaruhi hasil Olahraga Fisik dan Pendidikan Kesehatan sekitar 19,2%. (5) Perhatian orang tua dan kebugaran fisik tidak secara tidak langsung mempengaruhi hasil belajar Olahraga Fisik dan Pendidikan Kesehatan. (6) Perhatian orang tua dan motivasi belajar secara tidak langsung berpengaruh terhadap hasil belajar Pendidikan Olahraga dan Kesehatan Jasmani sebesar 16,9%. Kata kunci; Peranan Motivasi, Latihan Dalam meningkatkan, Kebugaran Jasmani.